EVALUASI KEBERHASILAN REALISASI DANA BOS SEBAGAI UPAYA PERBAIKAN KUALITAS PENDIDIKAN DI INDONESIA - Rediyanto Putra (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2022)
The education budget, which has a huge amount in 2020, is dominated by the Budget for Operational Assistance (BOS) funds. Therefore, this school operational assistance fund budget must be followed with optimal results. This paper aims to provide empirical evidence regarding the impact of the realization of BOS funds on the quality of education and HDI in Indonesia. This research was conducted in 33 provinces in Indonesia for the 2018-2019 period. The data in this study were obtained from data published by the Directorate General of Fiscal Balance and the Central Bureau of Statistics. Further research data were analyzed using path analysis through the Statistical Product and Service Solutions (SPSS) version 22.0 program. The results of the test show that the realization of BOS funds is proven to have a positive impact on increasing average school time so that it has an impact on increasing the Human Development Index. However, the test results have not been able to prove that the realization of BOS funds was able to significantly reduce the level of illiteracy in Indonesia. The significance that can be taken from the test results is (1) the realization of BOS funds has succeeded in improving the quality of education in Indonesia, however (2) the percentage of the total cost of BOS funds in the education budget needs to be readjusted with the other total education costs. Based on this, it is necessary to maximize the education budget postures.